Optimalisasi Pemenuhan Hak Pendidikan Anak di Lembaga Pembinaan Khusus Anak (LPKA) - Susanto Susanto (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Along with the state mandate through a number of regulations related to the importance of fulfilling the right to education for school-age children who are fostered by the Child Special Guidance Institution (LPKA) in Indonesia, the consequence is that optimizing the fulfillment of children's education rights must be ensured to run well. This study aims to determine the situation of fulfilling the right to education of school-age children in LPKA and the importance of optimizing the fulfillment of the right to education for LPKA children in Indonesia. This study uses a qualitative method. Data collection techniques through interviews, observations, questionnaires using google forms and document studies. The analysis in the study was carried out descriptively. This study found that the situation of fulfilling children's education rights in LPKA from the aspect of the education service system was 15% in the poor category, the aspect of the availability of educators 24% in the less category and the aspect of the availability of facilities and infrastructure in the 18% less category. As a solution, optimizing children's education services at LPKA should be carried out through 4 (four) main strategies, namely first, improving the quality of the education system, both ensuring the quality of formal education services and life skills education; second, improving the quality of educators by considering the fulfillment of the ratio and the relevance of the educational discipline of educators; third, improvement of facilities and infrastructure; Fourth, to create an environmental ecosystem with character, through various positive habituation efforts.